Enhancing microalgal biomass productivity by engineering a microalgal–bacterial community. (January 2015) - Cho, Dae-Hyun; Ramanan, Rishiram; Heo, Jina; Lee, Jimin; Kim, Byung-Hyuk; Oh, Hee-Mock; Kim, Hee-Sik
Highlights: Phycosphere bacterial diversity analyzed in C. vulgaris by DGGE and pyrosequencing. Growth promoting and inhibiting microorganisms from C. vulgaris were co-cultivated. Four isolated bacterial strains improved algal growth, flocculation and lipid content. Algae supplied DOC, bacteria in return, supplied DIC and low molecular weight DOC. Engineered consortium significantly enhanced algal biomass and lipid productivity. Abstract: This study demonstrates that ecologically engineered bacterial consortium could enhance microalgal biomass and lipid productivities through carbon exchange. Phycosphere bacterial diversity analysis in xenic Chlorella vulgaris (XCV) confirmed the presence of growth enhancing and inhibiting microorganisms. Co-cultivation of axenic C. vulgaris (ACV) with four different growth enhancing bacteria revealed a symbiotic relationship with each bacterium. An artificial microalgal–bacterial consortium (AMBC) constituting these four bacteria and ACV showed that the bacterial consortium exerted a statistically significant ( P < 0.05) growth enhancement on ACV. Moreover, AMBC had superior flocculation efficiency, lipid content and quality. Studies on carbon exchange revealed that bacteria in AMBC might utilize fixed organic carbon released by microalgae, and in return, supply inorganic and low molecular weight (LMW) organic carbon influencing algal growth and metabolism. Such exchanges, although species specific, have enormous significance in carbon cycle and can be exploitated by microalgal biotechnology industry.